2018
DOI: 10.3389/fendo.2018.00289
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Induced Limb Length Asymmetry Has Functional Impact on Weight Bearing in Mouse Hindlimbs

Abstract: Limb length inequality results from many types of musculoskeletal disorders. Asymmetric weight bearing from a limb length discrepancy of less than 2% can have debilitating consequences such as back problems and early-onset osteoarthritis. Existing treatments include invasive surgeries and/or drug regimens that are often only partially effective. As a noninvasive alternative, we previously developed a once daily limb-heating model using targeted heat on one side of the body for 2 weeks to unilaterally increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…In a model of heat-induced limb length asymmetry, the right sides of the body of the mice were positioned on a heating pad with a 40 °C constant temperature. For this purpose, isoflurane inhalation was used to hold the mice in lateral recumbency [ 67 ]. For Laser Doppler perfusion imaging of limbs, mice were lightly anesthetized by first inducing anesthesia in an induction chamber, and then by maintaining anesthesia by a nasal cannula delivering isoflurane/oxygen [ 63 ].Nerve transection on limbs may be performed on sciatic or femoral nerves.…”
Section: Maintenancementioning
confidence: 99%
“…In a model of heat-induced limb length asymmetry, the right sides of the body of the mice were positioned on a heating pad with a 40 °C constant temperature. For this purpose, isoflurane inhalation was used to hold the mice in lateral recumbency [ 67 ]. For Laser Doppler perfusion imaging of limbs, mice were lightly anesthetized by first inducing anesthesia in an induction chamber, and then by maintaining anesthesia by a nasal cannula delivering isoflurane/oxygen [ 63 ].Nerve transection on limbs may be performed on sciatic or femoral nerves.…”
Section: Maintenancementioning
confidence: 99%
“…Environmental temperature can affect bone remodeling, and exposure of growing mice to higher temperatures has shown to lengthen long bones (Racine et al, 2018 ). In a recent paper by Chevalier et al, warmth exposure (34°C) was reported to protect against ovariectomy-induced bone loss in mice.…”
Section: Confounding Factors and Recommendationsmentioning
confidence: 99%